EANO, SNO and Euracan consensus review on the current management and future development of intracranial germ cell tumors in adolescents and young adults. Issue 4 (1st November 2021) - Frappaz, Didier; Dhall, Girish; Murray, Matthew J; Goldman, Stuart; Faure Conter, Cecile; Allen, Jeffrey; Kortmann, Rolf Dieter; Haas-Kogen, Daphne; Morana, Giovanni; Finlay, Jonathan; Nicholson, James C; Bartels, Ute; et al.
Abstract: The incidence of intracranial germ cell tumors (iGCT) is much lower in European and North American (E&NA) than in Asian population. However, E&NA cooperative groups have simultaneously developed with success treatment strategies with specific attention paid to long-term sequelae. Neurological sequelae may be reduced by establishing a diagnosis with an endoscopic biopsy and/or cerebrospinal fluid (CSF) and/or serum analysis, deferring the need to perform a radical surgery. Depending on markers and/or histological characteristics, patients are treated as either germinoma or non-germinomatous germ cell tumors (NGGCT). Metastatic disease is defined by a positive CSF cytology and/or distant drops in craniospinal MRI. The combination of surgery and/or chemotherapy and radiation therapy is tailored according to grouping and staging. With more than 90% 5-year event-free survival (EFS), localized germinomas can be managed without aggressive surgery, and benefit from chemotherapy followed by whole ventricular irradiation with local boost. Bifocal germinomas are treated as non-metastatic entities. Metastatic germinomas may be cured with craniospinal irradiation. With a 5-year EFS over 70%, NGGCT benefit from chemotherapy followed by delayed surgery in case of residual disease, and some form of radiotherapy. Future strategies will aim at decreasing long-term side effects while preserving high cure rates.